2021
DOI: 10.1515/phon-2021-2003
|View full text |Cite
|
Sign up to set email alerts
|

Lexical analyses of the function and phonology of Papuan Malay word stress

Abstract: The existence of word stress in Indonesian languages has been controversial. Recent acoustic analyses of Papuan Malay suggest that this language has word stress, counter to other studies and unlike closely related languages. The current study further investigates Papuan Malay by means of lexical (non-acoustic) analyses of two different aspects of word stress. In particular, this paper reports two distribution analyses of a word corpus, 1) investigating the extent to which stress patterns may help word recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Only for cases in which stress cues are the only ones to reveal word identity, e.g., word disambiguation such as enforced in the current task, listeners show that they are able to use them. This result crucially complements the lexical analysis in Kaland and van Heuven (2020) and Kaland et al (2021), in which a representative subset of the Papuan Malay lexicon showed that stress information could have a facilitating effect word disambiguation, in addition to the segmental information. Although this facilitation is smaller in Papuan Malay than in languages with less regular stress patterns such as Spanish, the results showed that the Papuan Malay lexicon leaves room for a facilitating role of stress to a similar extent as found for English (Kaland & van Heuven, 2020;Kaland et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Only for cases in which stress cues are the only ones to reveal word identity, e.g., word disambiguation such as enforced in the current task, listeners show that they are able to use them. This result crucially complements the lexical analysis in Kaland and van Heuven (2020) and Kaland et al (2021), in which a representative subset of the Papuan Malay lexicon showed that stress information could have a facilitating effect word disambiguation, in addition to the segmental information. Although this facilitation is smaller in Papuan Malay than in languages with less regular stress patterns such as Spanish, the results showed that the Papuan Malay lexicon leaves room for a facilitating role of stress to a similar extent as found for English (Kaland & van Heuven, 2020;Kaland et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…This result crucially complements the lexical analysis in Kaland and van Heuven (2020) and Kaland et al (2021), in which a representative subset of the Papuan Malay lexicon showed that stress information could have a facilitating effect word disambiguation, in addition to the segmental information. Although this facilitation is smaller in Papuan Malay than in languages with less regular stress patterns such as Spanish, the results showed that the Papuan Malay lexicon leaves room for a facilitating role of stress to a similar extent as found for English (Kaland & van Heuven, 2020;Kaland et al, 2021). The results of the current study confirm that listeners are indeed able to rely on stress cues for word disambiguation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations